PREDIKSI PENYAKIT KARDIOVASKULER PADA TENAGA PENDIDIK DI SEKOLAH DASAR - Irawaty, Enny; Novendy; Iqram, Muhammad; Amadea, Stephanie (Jurnal Serina Abdimas, 2024)
Cardiovascular disease is one of the leading causes of death in Indonesia. According to Global Burden of Disease and Institute for Health Metrics and Evaluation data from 2014 to 2019, cardiovascular disease is the leading cause of death in Indonesia. Basic Health Research data for 2018 also reveal an increase in cardiovascular disease, with an incidence of 1.5% higher than the previous year, with an incidence of 0.5% lower in 2013. Teaching is a wonderful vocation, but the welfare of teachers, especially their health, receives little attention from many parties. Teachers may be unable to perform routine health exams, including analyzing the risk of heart disease, due to a lack of funds. As a result, the Faculty Medicine Universitas Tarumanagara health service staff took the initiative to conduct cardiovascular disease screenings. The Framingham Risk Score is a tool for determining the risk of cardiovascular disease. The activity was attended by 21 members of teacher. The participants' average age was 40.24 years, with a range of 30 to 56 years. Females made up 66.7% of all participants. The cardiovascular disease risk assessment revealed that practically all participants (90.5%) were at low risk. This is a good result, but you must be careful not to get overly optimistic about it. Routine checkups are still recommended to ensure good outcomes and avoid potential health problems.